PRODUCT DEVELOPMENT OF A WHEELCHAIR FOR DISABILITIES - Dian Palupi Restuputri; Giant Robby Nugroho (Center for Study and Journal Management FTI UMI, 2021)
Person with disabilities who are referred to as disabled people, are often regarded as unproductive citizens, unable to carry out their duties and responsibilities so that their rights are ignored. About 15 percent of the world's population are people with disabilities - more than one billion people. They are considered the largest minority group in the world. Persons with disabilities are often excluded from education, vocational training and employment opportunities. In reality, there are not many public facilities or special services provided to persons with disabilities. One of them is in the aspect of education. In public facilities, namely education, there are not many education buildings or educational providers that have facilities and infrastructure that can support people with disabilities. As for mobility equipment that can help people with disabilities on both legs, namely crutches, walking sticks, walkers, and wheelchairs that aim to help and facilitate their mobility. But the wheelchair that is available in the market today only has a limited function of moving left, right, and spinning, the function can not be maximized to help the movement of persons with disabilities there are some activities that cannot be done such as reaching higher objects, moving the body from a wheelchair to another seat, through the stairs / steps. Therefore we need a product design that starts from the preparation of product concepts from old products that will be modified into a new product to meet the needs of the market / people with disabilities.